Cost-effectiveness of ticagrelor plus aspirin versus aspirin in acute ischaemic stroke or transient ischaemic attack: an economic evaluation of the THALES trial - Yongjun Wang; S Claiborne Johnston; Pierre Amarenco; Carl Mellström; Mario Ouwens; Scott R Evans; Ritika Jain; Stefan James; Hans Denison; Per Ladenvall; Carlos A Molina; Anders Himmelmann; et al. (BMJ Neurology Open, 2023)
Objective THALES demonstrated that ticagrelor plus aspirin reduced the risk of stroke or death but increased bleeding versus aspirin during the 30 days following a mild-to-moderate acute non-cardioembolic ischaemic stroke (AIS) or high-risk transient ischaemic attack (TIA). There are no cost-effectiveness analyses supporting this combination in Europe. To address this, a cost-effectiveness analysis was performed.Methods Cost-effectiveness was evaluated using a decision tree and Markov model with a short-term and long-term (30-year) horizon. Stroke, mortality, bleeding and EuroQol-5 Dimension (EQ-5D) data from THALES were used to estimate short-term outcomes. Model transitions were based on stroke severity (disabling stroke was defined as modified Rankin Scale >2). Healthcare resource utilisation and EQ-5D data beyond 30 days were based on SOCRATES, another trial in AIS/TIA that compared ticagrelor with aspirin. Long-term costs, survival and disutilities were based on published literature. Unit costs were derived from national databases and discounted at 3% annually from a Swedish healthcare perspective.Results One-month treatment with ticagrelor plus aspirin resulted in 12 fewer strokes, 4 additional major bleeds and cost savings of €95 000 per 1000 patients versus aspirin from a Swedish healthcare perspective. This translated into increased quality-adjusted life-years (0.04) and reduced societal costs (−€1358) per patient over a lifetime horizon. Key drivers of cost-effectiveness were number of patients experiencing subsequent disabling stroke and degree of disability. Findings were robust over a range of input assumptions.Conclusion One month of treatment with ticagrelor plus aspirin is likely to improve outcomes and reduce costs versus aspirin in mild-to-moderate AIS or high-risk TIA.Trial registration number NCT03354429.